Students' Attitudes toward the Implementation of Imaginative Re-creation in Responding to Literary Works in Learning English in EFL Context - Muhammad Rifqi; Januarius Mujiyanto; Rudi Hartono; Sri Wuli Fitriati (International Conference on Science, Education, and Technology, 2022)
Teachers usually use literary texts in their English classes. They use such materials to teach reading comprehension but rarely combine them with writing. It is a big challenge for teachers to integrate reading and writing activities in the English classroom. Such action is demanding on the one hand, but it is challenging on the other hand. It is appealing because the teachers will burden much checking the students' reading comprehension and their response writing. It is challenging for teachers and students since it integrates reading and writing. This research was done in the context of English as a foreign language, where one hundred and twenty students of the "Literary Appreciation" course at the English Department of a private university in Semarang in 2020. In this research, we examined the students' attitudes toward applying imaginative re-creation in teaching English using short stories. Having done reading comprehension activities, the students wrote texts based on the short story they were assigned to read. The activity is called imaginative re-creation. At the end of the semester, a hundred and twenty students were involved in this research. Only forty-five students responded to the questionnaires. The questionnaires provided ten questions concerning the attitude toward applying imaginative re-creation. The results showed that the index is 3.7 indicating a strong attitude toward applying imaginative re-creation. From the findings, it can be concluded that most students had strong attitudes toward using literary text in English teaching, even though teachers should be aware of the problem that might arise during the implementation of the task.